2009
DOI: 10.1007/s11136-009-9549-0
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the Patient Activation Measure among individuals presenting for elective lumbar spine surgery

Abstract: The PAM is a reliable, valid measure of patient activation for individuals undergoing elective lumbar spine surgery and may have clinical utility in identifying those at risk for poor engagement in postsurgical rehabilitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
55
1
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(70 citation statements)
references
References 59 publications
8
55
1
6
Order By: Relevance
“…Our correlational findings are similar to Green (2010), who found positive relationships between hope and patient activation in another sample of people with mental illness, and to Skolasky et al (2009) who found positive relationships between hope and patient activation in another health condition (i.e., chronic back pain). That hope and patient activation are empirically related is consistent with studies emphasizing hope as an important factor for consumers' active engagement in recovery (Kirkpatrick et al, 2001;McCann, 2002).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our correlational findings are similar to Green (2010), who found positive relationships between hope and patient activation in another sample of people with mental illness, and to Skolasky et al (2009) who found positive relationships between hope and patient activation in another health condition (i.e., chronic back pain). That hope and patient activation are empirically related is consistent with studies emphasizing hope as an important factor for consumers' active engagement in recovery (Kirkpatrick et al, 2001;McCann, 2002).…”
Section: Discussionsupporting
confidence: 87%
“…Skolasky et al (2009) measured patient activation and psychological variables, including hope, optimism, self-efficacy, and locus of control in 283 people prior to surgery.…”
Section: Hope and Patient Activationmentioning
confidence: 99%
“…A literatura tem demonstrado os variados benefícios do estímulo ao autogerenciamento na saúde em indivíduos portadores de doenças crônicas (LORIG etal., 1999) e que existem relações significativas entre o índice de ativação e o comprometimento do indivíduo na realização de comportamentos saudáveis e preventivos de autogestão de sua saúde (HIBBARD et al, 2004;MOSEN et al, 2007;FOWLES et al, 2009;REMMERS et al 2009;SALYERS et al, 2009;ALEGRÍA et al, 2009;SKOLASKY et al, 2008;MAYBERRY et al, 2010;SKOLASKY et al, 2011;DONALD et al, 2011), às mudanças de comportamento que levam à melhor adesão ao tratamento (MOSEN et al, 2007;SKOLASKY et al, 2008;SKOLASKY et al, 2011), à melhoria da capacidade funcional e da qualidade de vida (STEPLEMAN et al, 2010;SKOLASKY et al, 2011) e à melhoria na autoeficácia e do estado emocional do indivíduo (SKOLASKY et al, 2009;STEPLEMAN et al, 2010 (HIBBARD et al, 2004).…”
Section: A Ativação Do Paciente Pode Ser Mensurada Com O Instrumento unclassified
“…Ao passo que períodos muito curtos podem sofrer influência de resultados contaminados pelo efeito recordatório, gerando superavaliação da estabilidade do teste (SILVA, RIBEIRO-FILHO, 2006;MARTINS, 2006;FAYERS;MACHIN, 2007;PASQUALI, 2009 sugere a literatura (MAGNESI, GLASSER, 2014;GREEN et al, 2010;STEPLEMAN et al;2010;SKOLASKY et al 2011;BRENK-FRANZ et al 2013;ZILL et al, 2013 MAGNESI;GLASSER, 2014;STEPLEMAN et al, 2010;SKOLASKY et al, 2008). (STEPLEMAN et al, 2010;SKOLASKY et al, 2009;MAGNESI;GLASSER, 2014;MUNCE et al, 2016).…”
Section: Na Validação Das Várias Versões Do Pam Os Autores Utilizaraunclassified
See 1 more Smart Citation